Breeding behaviour predicts patterns of natural hybridization in North American minnows (Cyprinidae). (21st December 2020) - Corush, Joel B.; Fitzpatrick, Benjamin M.; Wolfe, Elizabeth L.; Keck, Benjamin P.
Abstract: Premating barriers such as variation in reproductive behaviour can evolve quickly, but because gametic and postzygotic incompatibilities often evolve more slowly, circumstances that bring gametes into contact can breach the boundaries of premating isolation. In aquatic environments, the gametes of organisms with external fertilization are released into a constantly moving environment and may come into contact with heterospecific gametes. In fishes, nest association (spawning in another species' nest) is a behaviour that brings gametes from different species into close spatiotemporal proximity. These interactions might increase chances of hybridization, especially when multiple species associate with a single nest builder. This study addresses these interactions in the largest clade of North American freshwater fishes, the minnows (Cyprinidae). We compiled a list of over 17, 000 hybrid specimens in conjunction with species distribution data, breeding behaviours, and an inferred phylogeny to test if breeding behaviour, in addition to evolutionary history, is an important predictor of hybridization. We find that breeding behaviour is a significant predictor of hybridization, even when phylogenetic relatedness and divergence time are accounted for. Specifically, nest associates are more likely to hybridize with other nest associates whereas non‐nesting species had relatively low rates of hybridization.